Risk factors for local recurrence in Wilms tumour and the potential influence of biopsy – The United Kingdom experience. Issue 2 (January 2015) - Irtan, S.; Jitlal, M.; Bate, J.; Powis, M.; Vujanic, G.; Kelsey, A.; Walker, J.; Mitchell, C.; Machin, D.; Pritchard-Jones, K.; Renal Tumours Committee of the Children's Cancer and Leukaemia Group (CCLG)
Abstract Rationale The UKW3 trial compared biopsy/pre-operative chemotherapy versus immediate nephrectomy and afforded the opportunity to examine the influence of percutaneous retroperitoneal biopsy and other factors on local and distant relapse of Wilms tumour (WT). Methods Patients with unilateral WT (stages I–IV) excluding metachronous relapse or early progressive disease were eligible. Metastatic and 'inoperable' tumours were biopsied electively. 'Local' was defined as relapse within the abdomen, except for liver metastases considered as 'distant' relapse, together with other haematogenous routes. Uni- and multivariable analyses estimated the risk factors for relapse. Results Overall, 285/635 (44.9%) patients had a biopsy. With a median follow-up of 10.1 years, 35 (5.5%) patients experienced a 'local', 15 a combined (2.4%) and 60 (9.4%) a 'distant' relapse. On univariate analysis, biopsy, anaplasia and tumour size were associated with an increased risk of local relapse. On multivariable analysis, anaplasia and tumour size remained significant for local relapse whereas the elevated risk of biopsy (hazards ratio (HR) = 1.80: 95% confidence interval (CI) 0.97–3.32, p = 0.060) was marginal. Age, anaplasia, tumour size, lymph nodes metastases and stage, but not biopsy, were individually associated with increased risk of distant relapse but only age and anaplasia remained significant following multivariable analysis. Conclusions The UKW3 trial provides some reassurance that biopsy should not automatically lead to 'upstaging' of WT. Further assessment of this controversial area is required. Comparison of local relapse rates in a multinational trial in which the United Kingdom (UK) continued the practice of routinely biopsying all patients in contrast to the standard European approach will afford this opportunity and is planned.